Identitas Kultural Masyarakat Minahasa (Musik Mazani Pada Generasi Milenial) - Stefanny Mersiany Pandaleke; Meyltsan Herbert Maragani (Universitas Negeri Surabaya, 2022)
The artistic activity of the Minahasa community using Mazanias a vocal performance is unavoidable for the community, especially for the millennial generation. The profession of the millennial generation in Minahasa can no longer be generalized as farmers, which has an impact on the use of Mazani in daily activities. This research seeks to reveal how the community maintains Mazanias an identity of Minahasa through artistic activities for the millennial generation. This research uses a qualitative method with a cultural approach. The research design used is a case study, which was carried out in Minahasa Regency, North Sulawesi. Data collection techniques through observation, interviews, and document studies. The results indicate that there are three stages of forming the cultural identity of the Minahasa community using Mazani,namely (1) public perception of Mazani, (2) mindset of the Minahasa community, and (3) the sustainability of Mazaniin the millennial generation. Mazaniis an artistic act has been entrenched, a medium of communication and intermediary for the relationship between humans and God, as well as humans and each other. That perception determines the mindset of the Minahasa community that Mazanimust continue to be passed down from generation to generation. Performing arts are an effort by the Minahasa community to prioritize continue the cultural identity of the community from previous generation to the millennial generation.